Tomato productivity by arbuscular mycorrhizal in protected agriculture - Alvarado Carrillo, Manuel; Díaz Franco, Arturo; Peña del Río, María de los Ángeles (Revista Mexicana de Ciencias Agrícolas, 2018)
The effectiveness of arbuscular mycorrhizal fungi in crops under protected agriculture is poorly understood. The objective was to study the response of tomato (cv. 'El Cid') to mycorrhizal inoculation in a shade house structure. The seedlings were transplanted into soil, inoculated or not with Rhizophagus intraradices. The inoculated plants significantly increased chlorophyll content, plant height and root colonization compared with non-inoculated plants. Similarly, significant increases were observed in the length, diameter and fruit weight also increased fruit yield by cutting and accumulated in 30% yield. The beneficial effect of R. intraradices as promoter of tomato yield in protected agriculture may represent an efficient production management.
Keywords: mycorrhizal colonization; fruit characteristics; yield